2022
DOI: 10.1111/vde.13142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypochlorous acid as an ear flush in dogs with chronic otitis externa

Abstract: Background Chronic otitis externa (OE) in dogs frequently requires anaesthetised ear flushing. Objectives To evaluate hypochlorous acid as an ear flushing and antimicrobial agent in dogs with chronic OE. Animals Twenty dogs with chronic OE caused by the same organisms bilaterally. Materials and Methods One ear was flushed under anaesthesia with hypochlorous acid, the other with saline solution. Subsequently, the ear flushed with hypochlorous acid was cleaned with the same solution twice daily for 2 weeks, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Antimicrobial compounds in ear cleaners can retard microbial proliferation. Cleaners with isopropyl alcohol, parachlorometaxylenol (PCMX), chlorhexidine, hypochlorous acid and a low pH seem to be most effective [42][43][44] . TrisEDTA at 50mg/ml can show additive activity of with chlorhexidine, aminoglycosides and fluoroquinolones (see above).…”
Section: Epidermal Migration and Ear Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial compounds in ear cleaners can retard microbial proliferation. Cleaners with isopropyl alcohol, parachlorometaxylenol (PCMX), chlorhexidine, hypochlorous acid and a low pH seem to be most effective [42][43][44] . TrisEDTA at 50mg/ml can show additive activity of with chlorhexidine, aminoglycosides and fluoroquinolones (see above).…”
Section: Epidermal Migration and Ear Cleaningmentioning
confidence: 99%
“…A commercially available trisEDTA-NAC solution may facilitate removal and treatment of biofilms in ear canals, although time should be left between this and topical antibiotics as an in vitro study found most interactions between NAC and enrofloxacin or gentamicin were indifferent to antagonistic 49 . Other compounds with potential anti-biofilm and antimicrobial activity include chlorhexidine, polihexanide, hypochlorous acid 44,50 and trisEDTA 2 .…”
Section: Biofilmsmentioning
confidence: 99%